Sulfoxide-Directed Iterative Assembly into Oligoarenes - Yanagi, Tomoyuki; Nogi, Keisuke; Yorimitsu, Hideki (Synlett, 2020)
A series of oligoarenes have been synthesized via sulfoxide-based iterative dehydrogenative transformations. By utilizing the sulfinyl moieties as on/off-switchable directing groups, overreactions and/or undesired oligomerizations were completely suppressed. Since the dehydrogenative couplings were not hampered by steric hinderance, sterically encumbered oligoarenes were synthesized.
Keywords: iterative synthesis; sulfoxide; Pummerer reaction; [3,3] sigmatropic rearrangement; oligoarene